2014
DOI: 10.1179/1753807614y.0000000050
|View full text |Cite
|
Sign up to set email alerts
|

Lessons learned from The Black Cosmetologists Promoting Health Program: A randomized controlled trial testing a diabetes education program

Abstract: Purpose: Diabetes is reaching epidemic proportions in the United States and African Americans are at greater risk than most. Disparities in the incidence of diabetes place African American women at a much higher risk than their white counterparts. As such, the purpose of this study was to evaluate a community-based educational intervention program aimed at changing diabetes attitudes, knowledge, and screening behaviors of African American women via cosmetologists trained as community health educators. Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…Seven interventions focused on outcomes related to cancer [ 27 , 29 , 50 53 , 55 ], five on cardiovascular disease (i.e. blood pressure) [ 21 , 44 , 45 , 49 ], one on type 2 diabetes [ 30 ], and one on obesity [ 20 ]. Barbershops accounted for the majority of study settings ( n = 9) [ 21 , 44 , 45 , 50 53 , 55 , 56 ], with four studies taking place in hair salons [ 20 , 27 , 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Seven interventions focused on outcomes related to cancer [ 27 , 29 , 50 53 , 55 ], five on cardiovascular disease (i.e. blood pressure) [ 21 , 44 , 45 , 49 ], one on type 2 diabetes [ 30 ], and one on obesity [ 20 ]. Barbershops accounted for the majority of study settings ( n = 9) [ 21 , 44 , 45 , 50 53 , 55 , 56 ], with four studies taking place in hair salons [ 20 , 27 , 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…blood pressure) [ 21 , 44 , 45 , 49 ], one on type 2 diabetes [ 30 ], and one on obesity [ 20 ]. Barbershops accounted for the majority of study settings ( n = 9) [ 21 , 44 , 45 , 50 53 , 55 , 56 ], with four studies taking place in hair salons [ 20 , 27 , 29 , 30 ]. Interventions taking place in barbershops targeted men ( n = 9) [ 21 , 44 , 45 , 50 53 , 55 , 56 ] while those in hair salons targeted women ( n = 4) [ 20 , 27 , 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…32 Studies using hair stylists to deliver health communication around breast cancer screening and other health behaviours have shown promise due to the unique and close relationship African American women have with their stylist. [33][34][35][36][37][38] rationale Very few systematic reviews have looked at site or setting for engaging African Americans in health promotion, primarily focusing on 'cultural adaptions' of evidencebased interventions. [39][40][41][42][43] Of those that have, they were largely focused on recruitment strategies of participants for clinical trials from sites that include churches, barbershops and hair salons.…”
Section: Introductionmentioning
confidence: 99%
“…Another study led by the senior author demonstrated that repurposed, but comparable public health programs, may not necessarily achieve comparable outcomes [26]. Such findings underscore the importance of conducting preliminary demonstration studies to determine if there is sufficient evidence to warrant a larger, definitive research study.…”
Section: Introductionmentioning
confidence: 99%